Tahlîl al-Akhṭâ’ al-Nahwiyyah fî Qirâ’ah Kitab Fath al-Qarîb ladâ Ṭâlibât al-Ṣaf al-‘Alî - Luthfatul Qibtiyah; Sakinah Izzah Qorina (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2023)
Every santri has the ability to read, one of which is reading Arabic books such as the yellow book. Studying the yellow book is an important lesson in pesantren. Therefore, it is very important for santri to be able to read the yellow book correctly. However, there are still many mistakes in reading the yellow book, including errors in syntax errors (nahwu). This study aims to analyze syntactic errors in reading the book Fathul Qarib of santri of al-'Aali class at an-Najah I Karduluk Islamic Boarding School. In this study, researchers used a qualitative approach with descriptive research. The data collection methods used in this study were: observation, istima' method, interviews, and documentation. The data analysis used in this study is the steps developed by Ellis, namely: 1) Collecting data, 2) Defining errors, 3) Classifying errors, 4) Explaining errors, 5) Correcting errors. The results showed that the syntactic errors in reading the book Fath al-Qarib of santri of al-'Aali class at an-Najah I Karduluk Islamic boarding school, namely there were 56 errors in I'rab, 8 errors in Idhafah, and 17 errors in tawabi'. The factors that cause errors are differences in thinking ability, lack of concentration, and not repeating the lesson that has been obtained (muraja'ah).